Key determinants of marketing research effectiveness - Tarka, Piotr (Economics and Business Review, 2012)
In article the author presents his view and research findings based on conducted empirical studies. All issues are pertaining to marketing research problems, e.g., its effectiveness within a company's business environment. More interestingly this paper concerns key problems typical of the research industry. These issues form underlying conditions for constructing the process of valuable marketing research. In the first part of paper, the role of contemporary marketing research in business is described. Further on efficiency, effectiveness and measurability of the argued issues are described. Finally, key determinants of the research undertaken within companies are discussed, such as: management's attitude towards marketing research, macro and microeconomic factors affecting the research, diagnostic versus evaluative research problems, short and long-term components, and size of an organization. (original abstract)